Genetic information supports a causal relationship between trace elements, inflammatory proteins, and COPD: evidence from a Mendelian randomization analysis - Cao, Zhenghua; Zhao, Shengkun; Wu, Tong; Sun, Feng; Ding, Huan; Hu, Shaodan; Shi, Li (Frontiers in Nutrition, 2024)
Objective: Dietary factors and nutritional status may be among the risk factors for Chronic Obstructive Pulmonary Disease (COPD). There exists a certain correlation between trace elements and COPD. Through Mendelian Randomization (MR) analysis, we investigated the causal relationships between trace elements, inflammatory proteins, and COPD. Methods: We employed MR, multivariable MR (MVMR), and two-step MR (TSMR) approaches to assess the causal links between 15 trace elements and COPD, with 91 inflammatory proteins serving as mediators to further elucidate the tripartite causal relationships. Results: Trace elements such